Defining nucleic acid-binding properties of avian retrovirus integrase by deletion analysis. - Mumm, S R (1991)
Integration of retroviral DNA into the host genome requires the activity of retrovirus-encoded integration protein IN. We expressed Rous sarcoma virus (RSV) IN, 286 amino acid residues in length, by using in vitro transcription, followed by in vitro translation in rabbit reticulocyte lysate. The nucleic acid-binding activity of in vitro-translated IN was assessed by using DNA-cellulose affinity chromatography and poly(U)-Sepharose affinity chromatography and by sedimentation analysis in the presence or absence of DNA. In vitro-translated RSV IN exhibited nucleic acid-binding activity similar to that of IN purified from avian myeloblastosis virus. To identify regions of IN which bind to nucleic acids, several deletions of RSV IN were generated. The NH2-terminal 26 amino acids, including the two His residues of a His-Cys box, were not necessary for IN nucleic acid binding with any of the substrates tested. The substrates included native calf thymus DNA, poly(U), and a double-stranded linear DNA molecule with RSV long terminal repeat sequences at its termini. The COOH-terminal region (residues 178 to 286) of IN bound quantitatively (greater than 90%) to poly(U) and to single-stranded circular phi X174 DNA but did not exhibit the double-stranded linear DNA-binding ability of the entire IN molecule.